REVISIÓN DE LAS LICÓPSIDAS DE LA ARGENTINA. 2. MALANZANIA ARCHANGELSKY, AZCUY ETWAGNER y HAPLOSTIGMA SEWARD; CON NOTAS SOBRE CYCLOSTIGMA HAUGHTON (Ameghiniana, 2014)
"A dwarf Iycophyte from Devonian beds of the Río Blanco Basin, Haplostigma jurquei Frenguelli 1952, is described on the basis of the type specimens. They were found in beds belonging to the Chigua and Punilla Formations, of Middle-Late Devonian age. The stems have spirally disposed long, spine-like appendages which lack vascularisation. Comparison is made with other taxa, and a brief discussion is presented on the genus Haplostigma. The stratigraphic ranges and regional distribution are reported for Malanzania nana Archangelsky, Azcuy & Wagner 1981 (Upper Carboniferous), M. antiqua Archangelsky 1983 (Middle Devonian) and Haplostigma furquei Frenguelli 1952 (Middle to Upper Devonian). Cf. Archaeosigillaria sp. A (=""Asteroxylon sp."" sensu Frenguelli 1951), Archaeosigillaria sp. B and Lycophyte (""Gen. et sp. indet."") of Devonian and lowermost Upper Carboniferous strata of the San Juan Precordillera are also described. The reference of Argentine material to the genera Haplostigma Seward and Cyclostigma Haughton is discussed."